Augmented Reality With Semarang Historical Buildings to Enhance Students’ Geometry Modeling Skills - Arvangga Krisbiyantoro; Adi Nur Cahyono (Educia Journal, 2026)
Mathematical modeling still being a challenging competency for many student in secondary school level, especially in geometry where abstract spatial conception still difficult to connect with real-world situations. This study examined changes in students’ mathematical modeling skills following an AR-supported learning intervention integrated with Semarang City’s historical buildings on students mathematical modeling skills in geometry. Mix methods with sequential explanatory design was used involving 32 students that selected through purposive sampling. Quantitative data were collected using pretest and posttest modeling tasks that based on Gereja Blenduk, Lawang Sewu, and Tugu Muda as historical heritage, then analyzed using the Shapiro-Wilk test, paired sample t-test, and N-Gain. Qualitative data was gained from classroom observation and informal questioning in learning proses were analyzed to explain the quantitative findings. The results of test showed a significant improvement in students modeling skills (t(31) = 8.494,p < 0.001) with a medium N-Gain of 0.5755. AR supported visualization, problem identification, and mathematization, but students still experienced difficulties in validating and interpreting mathematical results in real world contexts.